2018
DOI: 10.1002/tea.21444
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about learning and enacted instructional practices: An investigation in postsecondary chemistry education

Abstract: While research on and development of evidence‐based instructional practices (EBIPs) in STEM education has flourished, implementation of these practices classrooms has not been as prolific. Using the teacher‐centered systemic reform model as a framework, we explore the connection between chemistry instructors’ beliefs about teaching and learning and self‐efficacy beliefs, and their enacted classroom practices. Postsecondary chemistry faculty present a unique population for the study because of their role in tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 81 publications
5
87
0
Order By: Relevance
“…In this work we argue that, in addition to elucidating specific barriers, an understanding of instructor's conceptions of writing and its utility is needed to fully explain the lack of adoption. This is because faculty's conceptions of writing instruction inform their use of writing in the classroom, just as they do for primary teachers (Graham, Harris, MacArthur, & Fink, ). For this reason, the study presented herein serves to bridge the gap between classroom writing and STEM research writing by exploring the relationship between STEM instructors’ conceptions of writing and their views of its role in the classroom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we argue that, in addition to elucidating specific barriers, an understanding of instructor's conceptions of writing and its utility is needed to fully explain the lack of adoption. This is because faculty's conceptions of writing instruction inform their use of writing in the classroom, just as they do for primary teachers (Graham, Harris, MacArthur, & Fink, ). For this reason, the study presented herein serves to bridge the gap between classroom writing and STEM research writing by exploring the relationship between STEM instructors’ conceptions of writing and their views of its role in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…The postsecondary classroom can be a site of increased disciplinary specialization and is often taught by a disciplinary expert (Coppola & Krajcik, ). Given the perspective of writing as a mode of disciplinary discourse (Airey & Linder, ) and the relationship between conceptions about teaching and enacted instructional practices (Gibbons, Villafañe, Stains, Murphy, & Raker, ), we investigated postsecondary instructors’ conceptions about writing in their classes to ultimately better understand how writing is incorporated into postsecondary STEM classes.…”
Section: Introductionmentioning
confidence: 99%
“…They point out that the four domains work in concert, meaning that internal motivations can be subverted by influencers like department chairs who do not support TPD, reward structures that do not support TPD, or personal issues that erode time to commit to TPD. Although this makes it seem like a hopeless confluence of barriers, positive personal beliefs and desires of instructors can override other barriers because of the strong role that beliefs play in instruction (Gess-Newsome et al, 2003;Andrews and Lemons, 2015;Robert and Carlsen, 2017;Gibbons et al, 2018). Indeed, Lund and Stains (2015) found that science faculty's adoption of evidence-based instructional practices was influenced by their beliefs about teaching.…”
Section: Barriers To Participating In Teaching Professional Developmentmentioning
confidence: 99%
“…2 Other educational research may be conducted in a chemistry course or setting for convenience but is not directly linked to the subject itself (i.e., collateral to CER); reports of these types of research are most suitable for general education research journals. 2,3 The areas of CER could include but are not limited to the following: laboratory learning, 4-7 pedagogy, 8 chemistry concepts and knowledge construction, [9][10][11][12] assessment, [13][14][15] technologies (broadly defined), [16][17][18] curriculum development, 19,20 emerging areas, 21,22 attitudes and beliefs (affect), [23][24][25][26] and equity, diversity, and inclusion. [27][28][29] Once an issue and research questions have been established, educational research is guided by one or more theoretical frameworks.…”
Section: What Is Cer?mentioning
confidence: 99%